Beyond emissions reduction: Climate change mitigation’s path to sustainable development - Gutierrez Zapata, Diana Maria; Vanegas Cubillos, Martha Cristina; Borda, Carlos Andrés; Casallas, Ivon Maritza; Sylvester, Janelle Marie; Castro Nunez, Augusto (2024)
Mitigating climate change isn't just about reducing greenhouse gas emissions, it's also about promoting sustainable economic development and improving people's well-being. Understanding and leveraging the co-benefits of climate change mitigation will advance the achievement of the SDGs by attracting finance, building support and informing strategic policy decisions.